Authenticity and nostalgia – subjective well-being of Chinese rural-urban migrants. Issue 5 (2nd November 2019) - Meng, Zhenhao (Mark); Cai, Liping A.; Day, Jonathan; Tang, Chun-Hung (Hugo); Lu, Ying (Tracy); Zhang, Hongmei
ABSTRACT: This study investigates the subjective well-being of Chinese rural-urban migrants by examining the effects of nostalgia and perceived authenticity in the context of rural tourism. Founded on the concepts of tourist motivation and nostalgia and drawn on selected Chinese philosophical values, this study identifies the unique Chinese philosophical value of 'old home' as the key factor of motivation for migrants returning to rural destinations. Rural-urban migrants deem rural regions, as well as, mentalities, cultures, and environments in general, as their cultural and spiritual hometowns. The study also reveals that migrants pursue authentic rural destinations, which would have an emotional and memorable appeal, because it stimulates their nostalgic feelings. The study proposes the necessity of investigating Chinese issues through the lens of Chinese philosophical values and invokes an age-old value to understand their perception process of authenticity: 'one can't have fish and bear at the same time.' Returning to rural destinations improves these tourists' subjective well-being because they achieve an important lifetime goal based on their traditional Chinese philosophical value of 'searching for ancestral roots.' The study suggests that preserving rural authenticity can improve the social and cultural welfare of hosting communities and the subjective well-being of tourists.